Cathepsin S inhibition combines control of systemic and peripheral pathomechanisms of autoimmune tissue injury - Maia Tato (Nature Portfolio, 2017)
Abstract Cathepsin(Cat)-S processing of the invariant chain-MHC-II complex inside antigen presenting cells is a central pathomechanism of autoimmune-diseases. Additionally, Cat-S is released by activated-myeloid cells and was recently described to activate protease-activated-receptor-(PAR)-2 in extracellular compartments. We hypothesized that Cat-S blockade targets both mechanisms and elicits synergistic therapeutic effects on autoimmune tissue injury. MRL-(Fas)lpr mice with spontaneous autoimmune tissue injury were treated with different doses of Cat-S inhibitor RO5459072, mycophenolate mofetil or vehicle. Further, female MRL-(Fas)lpr mice were injected with recombinant Cat-S with/without concomitant Cat-S or PAR-2 blockade. Cat-S blockade dose-dependently reversed aberrant systemic autoimmunity, e.g. plasma cytokines, activation of myeloid cells and hypergammaglobulinemia. Especially IgG autoantibody production was suppressed. Of note (MHC-II-independent) IgM were unaffected by Cat-S blockade while they were suppressed by MMF. Cat-S blockade dose-dependently suppressed immune-complex glomerulonephritis together with a profound and early effect on proteinuria, which was not shared by MMF. In fact, intravenous Cat-S injection induced severe glomerular endothelial injury and albuminuria, which was entirely prevented by Cat-S or PAR-2 blockade. In-vitro studies confirm that Cat-S induces endothelial activation and injury via PAR-2. Therapeutic Cat-S blockade suppresses systemic and peripheral pathomechanisms of autoimmune tissue injury, hence, Cat-S is a promising therapeutic target in lupus nephritis.